Highly Durable Fluorinated High Oxygen Permeability Ionomers for Proton Exchange Membrane Fuel Cells. Issue 45 (17th October 2022) - Macauley, Natalia; Lousenberg, Robert D.; Spinetta, Magali; Zhong, Sichen; Yang, Fan; Judge, Will; Nikitin, Viktor; Perego, Andrea; Qi, Yongzhen; Pedram, Sara; Jankovic, Jasna; Zenyuk, Iryna V.; et al.
Abstract: For proton exchange membrane fuel cells to be cost‐competitive in light‐ and heavy‐duty vehicle applications, their Pt content in the catalyst layers needs to be lowered. However, lowering the Pt content results in voltage losses due to high local oxygen transport resistances at the ionomer–Pt interface. It is therefore crucial to use ionomers that have higher oxygen permeability than Nafion. In this work, novel high oxygen permeability ionomers (HOPIs) are presented, with up to five times higher oxygen permeability than Nafion, synthesized by copolymerization of perfluoro‐2, 2‐dimethyl‐1, 3‐dioxole (PDD) with perfluoro(4‐methyl‐3, 6‐dioxaoct‐7‐ene) sulfonyl fluoride (PFSVE). PDD is the source of higher permeability due to its open ring structure, while PFSVE provides ionic conductivity. Optimization of PDD content and equivalent weight enables increased fuel cell performance, mainly at high current densities, where HOPIs can achieve power densities >1.25 W cm −2 and exceed the 0.8 A cm −2 U.S. Department of Energy durability target by losing only 4.5 mV, which is over six times less than 30 mV. The interactions between HOPI and SO3 − groups with a PtCo/C catalyst are also elucidated here at a fundamental level. Abstract : Robust high oxygen permeability ionomers synthesized and integrated into proton exchange membrane fuel cell catalyst layers form high power‐density membrane electrode assemblies with exceptional durability showing extremely low local oxygen transport resistance with uniform ionomer distribution, achieves power densities above 1.25 W cm 2 and >3× lower voltage loss at 0.8 A cm −2 than Nafion after 30 000 AST cycles.